Cadmium induces apoptosis via generating reactive oxygen species to activate mitochondrial p53 pathway in primary rat osteoblasts. (15th December 2020) - Zheng, Jiaming; Zhuo, Liling; Ran, Di; Ma, Yonggang; Luo, Tongwang; Zhao, Hongyan; Song, Ruilong; Zou, Hui; Zhu, Jiaqiao; Gu, Jianhong; Bian, Jianchun; Yuan, Yan; et al.
Abstract: Cadmium (Cd), a heavy metal produced by various industries, contaminates the environment and seriously damages the skeletal system of humans and animals. Recent studies have reported that Cd can affect the viability of cells, including osteoblasts, both in vivo and in vitro. However, the mechanism of Cd-induced apoptosis remains unclear. In the present study, primary rat osteoblasts were used to investigate the Cd-induced apoptotic mechanism. We found that treatment with 2 and 5 μM Cd for 12 h decreased osteoblast viability and increased apoptosis. Furthermore, Cd increased the generation of reactive oxygen species (ROS), and, thus, DNA damage measured via p-H2AX. The level of the nuclear transcription factor p53 was significantly increased, which upregulated the expression of PUMA, Noxa, Bax, and mitochondrial cytochrome c, downregulated the expression of Bcl-2, and increased the level of cleaved caspase-3. However, pretreatment with the ROS scavenger N -acetyl-l -cysteine (NAC) or the p53 transcription specific inhibitor PFT-α suppressed Cd-induced apoptosis. Our results indicate that Cd can induce apoptosis in osteoblasts by increasing the generation of ROS and activating the mitochondrial p53 signaling pathway, and this mechanism requires the transcriptional activation of p53.